Greenwood : a novel - Christie, Michael, 1976- (London ; New York : Hogarth, 2020)
"It's 2034 and Jake Greenwood is a storyteller and a liar, an overqualified tour guide babysitting ultra-rich vacationers in one of the world's last remaining forests. It's 2008 and Liam Greenwood is a carpenter, fallen from a ladder and sprawled on his broken back, calling out from the concrete floor of an empty mansion. It's 1974 and Willow Greenwood is out of jail, free after being locked up for one of her endless series of environmental protests: attempts at atonement for the sins of her father's once vast and violent timber empire. It's 1934 and Everett Greenwood is alone, as usual, in his maple syrup camp squat when he hears the cries of an abandoned infant and gets tangled up in the web of a crime that will cling to his family for decades. And throughout, there are trees: thrumming a steady, silent pulse beneath Christie's effortless sentences and working as a guiding metaphor for withering, weathering, and survival. A shining, intricate clockwork of a novel, Greenwood is a rain-soaked and sun-dappled story of the bonds and breaking points of money and love, wood and blood--and the hopeful, impossible task of growing toward the light"--.
new book 2022 fall.
Keywords: Sagas; Family life; Literary; Historical; Domestic fiction